2016
DOI: 10.1371/journal.pone.0167039
|View full text |Cite
|
Sign up to set email alerts
|

Budget Impact of Long-Acting Insulin Analogues: The Case in Brazil

Abstract: BackgroundLong-acting insulin analogues for type 1 diabetes (T1D) treatment have been available on the Brazilian market since 2002. However, the population cannot access the analogues through the public health system.ObjectiveTo estimate the incremental budget impact of long-acting insulin analogues coverage for T1D patients in the Brazilian public health system compared to NPH insulin.MethodsWe performed a budget impact analysis of a five-year period. The eligible population was projected using epidemiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 34 publications
(42 reference statements)
0
14
0
1
Order By: Relevance
“…The speed with which evidence is produced and the pressure for incorporation discourage a conservative approach to the use of technologies. Rapid-and slow-acting insulins, for example, which are leading objects of lawsuits against SUS, were incorporated, even after several studies that showed the lack of gains in effectiveness from the system's perspective (De Souza et al, 2014;Laranjeira et al, 2016;Chieffi et al, 2017;CONITEC, 2019a;CONITEC, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…The speed with which evidence is produced and the pressure for incorporation discourage a conservative approach to the use of technologies. Rapid-and slow-acting insulins, for example, which are leading objects of lawsuits against SUS, were incorporated, even after several studies that showed the lack of gains in effectiveness from the system's perspective (De Souza et al, 2014;Laranjeira et al, 2016;Chieffi et al, 2017;CONITEC, 2019a;CONITEC, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the studies (n = 11) were from Europe and the U.S., of which five studies were conducted in US (20,(24)(25)(26)(27), two in Italy (14,22), one in Netherlands (19), one in Spain (18), one in England (13)and one in Bosnia and Herzegovina (15). Apart from these, three studies were conducted in China (10)(11)(12), two in Brazil (21,23), one in Egypt (17) and one in Thailand (16). Among the 18 studies, most of them (n = 11) were conducted from a payer's perspective and a few studies (n = 5) from the perspective of health care system, while one study (17) was conducted from both of the payer and social perspectives.…”
Section: Data Extractionmentioning
confidence: 99%
“…The majority of studies (n = 15) focused on BIA only, while the other studies (n = 3) combined the BIA with cost-effectiveness analysis. About half of the BIA studies (n = 8) evaluated the budget impact of insulin, including basal insulin (n = 5) (13,(20)(21)(22)26), pre-mix insulin (n = 1) ( 16), bolus insulin (n = 1) (24). One study focused on the administration route of insulin (continuous subcutaneous insulin infusion vs. multiple daily insulin injections) instead of the specific type of insulin (18).…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…De maneira exemplificativa, apresentamos na Tabela 45 as marcas requisitadas para itens disponibilizados nas três listas do SUS.Tabela 45 -Requisição Marca Específica -Lista de Componentes SUS 2019) 7 . De todo modo, a comparação é relevante e os resultados encontrados estão, ainda, em linha com conclusões de estudos que avaliaram o custo de incorporação da insulina análoga no mundo (LARANJEIRA; SILVA;PEREIRA, 2016;SOPPI et al, 2018). o intuito de apresentar a participação de médicos e advogados, segregados por agentes privados versus públicos nessa judicialização, por portadores de DM, contra o Estado.…”
unclassified